HUBUNGAN PENGETAHUAN SDKI, SLKI DAN SIKI TERHADAP PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUMAH SAKIT BENYAMIN GULUH KOLAKA - Ekawati Saputri; Evodius Nasus; Grace Tedy Tulak (Nusantara Hasana Journal, 2025)
Nursing care documentation based on the Indonesian Nursing Diagnosis Standards (SDKI), Indonesian Nursing Outcome Standards (SLKI), and Indonesian Nursing Intervention Standards (SIKI) plays a crucial role in ensuring quality and patient safety. This study aimed to examine the relationship between nurses’ knowledge of SDKI, SLKI, and SIKI and the implementation of nursing care documentation at Benyamin Guluh Kolaka Hospital. A descriptive analytic design with a cross-sectional approach was employed. A total of 53 nurses were selected using purposive sampling. Data were collected through a knowledge questionnaire and a nursing care documentation questionnaire. Data analysis consisted of univariate and bivariate analyses using Spearman’s Rho test. The results indicated that most nurses had good levels of knowledge and nursing documentation performance. However, statistical analysis revealed no significant relationship between nurses’ knowledge and nursing care documentation (p = 0.503; r = −0.094). This study concludes that nursing documentation quality is not solely determined by knowledge but is also influenced by other factors in nursing practice.